Design of optoelectronic system for optical diffusion tomography; MATEC Web of Conferences; Vol. 102 : Space Engineering - Erakhtin I. Igor; Aristov A. A. Aleksandr Aleksandrovich; Novoseltseva A. Anna; Sukhanov V. Viktor (2017, 2017)
Title screen